Participatory forest management, equity and local governance – keynote address - Colfer, C.J.P.; Komarudin, Heru; German, L.; Nyangas, S.; Siagian, Y.; Tanui, J. (Ministry of Agriculture and Rural Development of Ethiopia with other stakeholders, 2007)
This paper briefly reviews CIFOR’s experience using participatory action research working with communities, user groups within communities, and with governments at various levels, in Bolivia, Brazil, Cameroon, Ghana, Indonesia, Kyrgyzstan, Madagascar, Malawi, Nepal, Philippines, and Zimbabwe. The most dramatic changes that took place early on included increases in knowledge about social and ecological systems and improved skills in conflict management, negotiation, and facilitation. Longer term evaluation will be necessary to confirm actual ecological improvement, and the institutionalization of adaptive mechanisms (planning, implementing monitoring, revising plans). Emphasis is placed on the most recent findings, in second stage work, from CAPRi (Collective Action and Property Rights) research in Asia and Africa. This paper examines some of the successes and difficulties faced working with governmental stakeholders. Successes were most apparent in attitudinal changes, increased capacity for reflection and analysis, improvements in proposal writing and networking at larger scales. Difficulties included frequent personnel shifts, traditional bureaucratic concerns about 'turf', and budgetary inflexibilities. The paper concludes by proposing some important areas for future concentration of effort, including better attention to the various groups that exist within communities, more attention to the links between communities and other stakeholders, and training or awareness raising for government officials on methods for working more effectively and equitably with communities.